Islamic Brand Pada Era Revolusi Industri 5.0 - Kholishudin, Kholishudin; Rikantasari, Shelvyna (Universitas Islam Negeri Sumatera Utara, 2024)
This article discusses the phenomenon that is developing in society regarding Islamic brands in the era of the industrial revolution 5.0 which is currently developing. The labeling